Randomized controlled trial of deutetrabenazine for tardive dyskinesia: The ARM-TD study - Fernandez, Hubert H. (Neurology, 2017)
OBJECTIVE: To determine the efficacy and safety of deutetrabenazine as a treatment for tardive dyskinesia (TD). METHODS: One hundred seventeen patients with moderate to severe TD received deutetrabenazine or placebo in this randomized, double-blind, multicenter trial. Eligibility criteria included an Abnormal Involuntary Movement Scale (AIMS) score of ≥6 assessed by blinded central video rating, stable psychiatric illness, and stable psychoactive medication treatment. Primary endpoint was the change in AIMS score from baseline to week 12. Secondary endpoints included treatment success at week 12 on the Clinical Global Impression of Change (CGIC) and Patient Global Impression of Change. RESULTS: For the primary endpoint, deutetrabenazine significantly reduced AIMS scores from baseline to week 12 vs placebo (least-squares mean [standard error] −3.0 [0.45] vs −1.6 [0.46], p = 0.019). Treatment success on CGIC (48.2% vs 40.4%) favored deutetrabenazine but was not significant. Deutetrabenazine and placebo groups showed low rates of psychiatric adverse events: anxiety (3.4% vs 6.8%), depressed mood/depression (1.7% vs 1.7%), and suicidal ideation (0% vs 1.7%, respectively). In addition, no worsening in parkinsonism, as measured by the Unified Parkinson's Disease Rating Scale motor subscale, was noted from baseline to week 12 in either group. CONCLUSIONS: In patients with TD, deutetrabenazine was well tolerated and significantly reduced abnormal movements. CLASSIFICATION OF EVIDENCE: This study provides Class I evidence that in patients with TD, deutetrabenazine reduces AIMS scores.